Model Keterlibatan Perguruan Tinggi Dalam Pengembangan Pangan Lokal - Fitriani Fitriani; Edoardus E Maturbongs (SOCIETAS, 2021)
People who lived in Papua used to consume non-rice carbohydrate sources, but now they are consumingrice. Merauke Regency is designated nationally as a granary for eastern Indonesia. This conditionreduces the development of food diversification based on local resources. One of the universities inMerauke Regency is Musamus University, where the role is needed by the local community in the contextof preserving and developing local food. This study aims to create a model for the involvement of stateuniversities, especially Unmus in the context of developing local resource-based food. The researchmethod used is qualitative research methods. The research was conducted by involving academics (IBTUnmus) and the community in local villages around Merauke City (Wapeko, Yanggandur, Sota) to jointlyanalyze the problems in the form of FGD (focus group discussion) activities and interviews. Theanalytical methods used in the research generally include qualitative descriptive analysis (rational policymodels) and strategy analysis which is carried out using the SWOT method. The results of this studyfound 4 (four) main activities, namely (1) Research Topics, (2) Sustainable Education / Training /Socialization, (3) Sustainable Assistance, (4) Local Food Marketing Center. In this model, it can also beseen that there are external factors that affect the involvement of the university specifically MusamusUniversity in the development of local food in Merauke Regency.